Depressive symptoms homophily among community-dwelling older adults in japan: A social networks analysis - Morita, Ayako; Takahashi, Yoshimitsu; Takahashi, Kunihiko; Fujiwara, Takeo (Frontiers in Public Health, 2022)
Abstract Late-life depression is one of the common mental illnesses that cause serious consequences but the majority do not reach out for mental health services and relapses are common. The present study investigated profiled similarity of older adults’ social networks in terms of depressive symptoms. In 2017, we distributed questionnaires to community-dwelling older adults in a small city (Wakuya, Miyagi prefecture, Japan) inquiring demographics, functional status, overall and specific depressive symptoms (GDS-15) and nomination of confidants in the community. Applying the Exponential Random Graph Model, we estimated the likelihood of forming strong social ties by similarity on GDS-15 total and subscale scores within 660 respondents eligible for analysis (i.e., 217,470 potential ties). The probability of forming a strong tie was decreased by 5% with one score difference between nodes in overall depressive symptoms (odds ratio [OR], 0.95; 95% confidence interval [CI], 0.90 - 1.00). With respect to specific depressive symptoms, the probability of a strong tie formation was significantly decreased by 19% with one score difference in apathy symptoms (OR, 0.81; 95%CI, 0.67 - 0.98) but it was not significantly associated with differences in suicidal ideation (OR, 1.00; 95%CI, 0.87 - 1.14). These findings suggest depression homophily in social networks of community-dwelling older adults and the importance of network intervention in preventing late-life depression.